A Dual-Color Far-Red to Near-Infrared Firefly Luciferin Analogue Designed for Multiparametric Bioluminescence Imaging** - Jathoul, Amit P (Angew Chem Int Ed Engl, 2014)
Red-shifted bioluminescent emitters allow improved in vivo tissue penetration and signal quantification, and have led to the development of beetle luciferin analogues that elicit red-shifted bioluminescence with firefly luciferase (Fluc). However, unlike natural luciferin, none have been shown to emit different colors with different luciferases. We have synthesized and tested the first dual-color, far-red to near-infrared (nIR) emitting analogue of beetle luciferin, which, akin to natural luciferin, exhibits pH dependent fluorescence spectra and emits bioluminescence of different colors with different engineered Fluc enzymes. Our analogue produces different far-red to nIR emission maxima up to λ(max)=706 nm with different Fluc mutants. This emission is the most red-shifted bioluminescence reported without using a resonance energy transfer acceptor. This improvement should allow tissues to be more effectively probed using multiparametric deep-tissue bioluminescence imaging.